2022
DOI: 10.21009/ijlecr.v8i2.32013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Video Games in Learning English

Abstract: The aim of this study was to elucidate the role of video games as medium to be applied in a technique of learning English in Indonesia. Playing games has a vital role as a means of enhancing learners' reading, writing, listening, and speaking capabilities. In addition, video games offer unique opportunities for learners to master English grammar and expand their vocabularies. Furthermore, playing video games has a pivotal role in motivating EFL learners to communicate using EFL through their challenges, active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…The results from this study concurred with the study from Zamzami & Zamzami (2023), who added the value of exposing children to cartoon media content as it improves children's vocabularies and understanding of those vocabularies-in the view of Seli and Santosa (2022) added that visual aids such as cartoons have proven to effective in facilitating language acquisition to children as they are more engaging and interactive. Moreover, Rasyid (2016) revealed that cartoons play a significant role in ensuring children master a variety of vocabulary quickly.…”
Section: Edu-cartoons Increase Vocabulariessupporting
confidence: 87%
“…The results from this study concurred with the study from Zamzami & Zamzami (2023), who added the value of exposing children to cartoon media content as it improves children's vocabularies and understanding of those vocabularies-in the view of Seli and Santosa (2022) added that visual aids such as cartoons have proven to effective in facilitating language acquisition to children as they are more engaging and interactive. Moreover, Rasyid (2016) revealed that cartoons play a significant role in ensuring children master a variety of vocabulary quickly.…”
Section: Edu-cartoons Increase Vocabulariessupporting
confidence: 87%
“…Moreover (Gómez Chova et al, 2015) argue that the use of video in teaching and learning activities has become increasingly important for several reasons. Firstly, it can facilitate thinking and problem-solving by making connections between visual clues, memory processes, and the recall of new knowledge (Seli & Santosa, 2022).…”
Section: The Utilization Of Videos In An Educational Settingmentioning
confidence: 99%
“…Employing visual aids, such as podcasts and videos, is a popular, innovative approach to deliver English language material to students, since it captures their attention and interest. Videos, in particular, are a valuable tool as they can help students develop integrated skills in reading, writing, speaking, and listening in a single package (Seli & Santosa, 2022). Using videos as a language learning tool can significantly help young learners develop their English skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation